2020
DOI: 10.1017/cjn.2020.79
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Deep Brain Stimulation Use for Parkinson’s Disease in Ontario, Canada

Abstract: Objective: To examine whether sociodemographic characteristics and health care utilization are associated with receiving deep brain stimulation (DBS) surgery for Parkinson’s disease (PD) in Ontario, Canada. Methods: Using health administrative data, we identified a cohort of individuals aged 40 years or older diagnosed with incident PD between 1995 and 2009. A case-control study was used to examine whether select factors were associated with DBS for PD. Patients were classified as cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…For example, DBS surgery has been related to living in neighborhoods with high socioeconomic status 30 or predominantly Caucasian neighborhoods. 28 Most participants in the PPMI cohort (92%) are white and this may partially explain the greater than expected proportion of DBS+ patients. In this cohort, we did not observe differences in ethnicity, but the lack of ethnic diversity in this group limits our ability to detect such differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DBS surgery has been related to living in neighborhoods with high socioeconomic status 30 or predominantly Caucasian neighborhoods. 28 Most participants in the PPMI cohort (92%) are white and this may partially explain the greater than expected proportion of DBS+ patients. In this cohort, we did not observe differences in ethnicity, but the lack of ethnic diversity in this group limits our ability to detect such differences.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is likely their awareness of DBS is higher, and they may have more access to surgical options. Indeed, having more frequent access to a neurologist 28 has been associated with an increased chance of DBS surgery. Possibly related to this, sex did not play a significant role in eventual DBS surgery (DBS+ 37% female, DBS− 35% female).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this is not the case. Crispo and colleagues (2020) demonstrated that PD patients living in Ontario neighborhoods with the highest concentration of visible minorities were less likely to receive DBS than those living in predominantly white neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…8 Crispo and colleagues reported significant regional variation in DBS implantation rates in Ontario. 9 Recently, two priority areas that have been identified for neuroethical inquiry are "issues of equity, resource allocation, and distributive justice" 10 and the cultural meanings of advanced neurotechnologies. 11 To our knowledge, no Canadian study has looked at whether access may differ across the lines of race, ethnicity or culture, or applied qualitative methods to investigate access disparities.…”
Section: Introductionmentioning
confidence: 99%
“…This gap is significant because the varying definitions of rural and remote and the size of populations can impact results and conclusions derived from quantitative models. 9,12 Case Study…”
Section: Introductionmentioning
confidence: 99%